Stoneflies (Plecoptera) of Crimea - L.A. Zhiltzova; G.A. Prokopov (Кавказский энтомологический бюллетень, 2016)
The historical review of study of Crimean Plecoptera is given. At present time 9 species belonging to the 7 genera from 7 families are known from Crimea